Donald Creighton : A Life in History - Wright, Donald A., 1965- (Book collections on Project MUSE., 2015)
Through his virtuoso research into Creighton's own voluminous papers, Donald Creighton captures the twentieth-century transformation of English Canada through the life and times of one of its leading intellectuals.